Indirect calorimetry versus usual care: a retrospective cohort study. - Sanjith Saseedharan; Roopa Karanam; Vaijayanti Kadam; Annapurna Chiluka; Elizabeth Mathew (Critical Care Innovations, 2022)
NTRODUCTION: : This is a study evaluating the effect of Indirect calorimetry on the length of stay. The study comprises of the comparison between the use of indirect calorimetry versus usual care in critically ill mechanically ventilated patients with respect to the length of stay in the intensive care unit, and duration of time on ventilator. Patients were divided on basis of their nutrition risk to study the effect of Indirect calorimetry on the length of stay. MATERIAL AND METHODS: This was a retrospective cohort study of 166 mechanical ventilated patients in S .L Raheja Hospital. Data was collected from 83 patients who were mechanically ventilated between January 2019 and November 2019 on whom indirect calorimetry was used to measure energy requirements. This cohort was compared to 83 patients between January 2018 and November 2918 where the energy requirements were calculated with the use of predictive equations. Both groups were matched for age, sex, comorbidities, APACHE score and use of vasopressors. RESULTS: Significant difference in the sicker group of patients was seen in the Length of stay in the intensive care unit. (9.23 ± 8.14 vs. 11.52 ± 5.65, p = 0.0034) Patients at risk for malnutrition demonstrated reduced length of time on ventilation as compared to those not at risk. (10.2 ± 11.01 vs. 13 ± 5.87; p = 0.0042). CONCLUSIONS: The use of indirect calorimetry may be associated with a lower length of ICU stay among ventilated patients in a reasonably sick group of mixed surgical patients.